2018
DOI: 10.1186/s13662-017-1458-x
|View full text |Cite
|
Sign up to set email alerts
|

A model of HIV/AIDS population dynamics including ARV treatment and pre-exposure prophylaxis

Abstract: Antiretroviral treatment (ART) and oral pre-exposure prophylaxis (PrEP) have recently been used efficiently in management of HIV infection. Pre-exposure prophylaxis consists in the use of an antiretroviral medication to prevent the acquisition of HIV infection by uninfected individuals. We propose a new model for the transmission of HIV/AIDS including ART and PrEP. Our model can be used to test the effects of ART and of the uptake of PrEP in a given population, as we demonstrate through simulations. The model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
0
6
0
3
Order By: Relevance
“…The proof by contradiction that we use towards Theorem 2.2 has been popularly used, for instance, in [ 12 ] and [ 14 ].…”
Section: The Modelmentioning
confidence: 99%
“…The proof by contradiction that we use towards Theorem 2.2 has been popularly used, for instance, in [ 12 ] and [ 14 ].…”
Section: The Modelmentioning
confidence: 99%
“…Their numerical simulations showed that the epidemic spread could be controlled thanks to vaccination, even if the basic reproduction number remains above 1. In [7,8], an explicit PrEP compartment was included in the SICA model. The parameters in [8] were adjusted with clinical data and PrEP's effectiveness mathematically proven.…”
Section: Introductionmentioning
confidence: 99%
“…HIV slowly deprives the immune function and increases the risk of infection with a variety of other diseases. Despite new scientific progress and a series of public health interventions, AIDS remains one of the most devastating diseases in human history 2 . Globally, 37.9 million people were living with HIV at the end of 2018 and 770,000 people died of HIV‐related illnesses worldwide in 2018 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite new scientific progress and a series of public health interventions, AIDS remains one of the most devastating diseases in human history. 2 Globally, 37.9 million people were living with HIV at the end of 2018 and 770,000 people died of HIV-related illnesses worldwide in 2018. 3 There is still a lack of effective drugs to eradicate HIV infection worldwide.…”
Section: Introductionmentioning
confidence: 99%